2022
DOI: 10.1088/1361-665x/ac5860
|View full text |Cite
|
Sign up to set email alerts
|

High torque density magnetorheological brake with multipole dual disc construction

Abstract: This paper presents a magnetorheological (MR) brake with the intent of overcoming the problems of limited torque density and low manufacturability that conventional MR brakes come across. Firstly, the conceptual design of the proposed MR brake was finalized. High torque density was achieved by using the combined effect of the dual disc-type construction and multipole concept. High manufacturability was attained with a simple and lightweight mechanical construction. It was created with the major components, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…The proposed MR clutch in this paper are compared with the typical MR devices (Lord RD-2087-01 [41], Serpentine MR brake [42], Multi-pole bilayer MR brake [27], Multipole dual disc [43]) presented in the state of art is necessary. Table 3 compares the design specifications of the proposed MR clutch to the existing MR devices in the literature.…”
Section: Torque Experiments Resultsmentioning
confidence: 99%
“…The proposed MR clutch in this paper are compared with the typical MR devices (Lord RD-2087-01 [41], Serpentine MR brake [42], Multi-pole bilayer MR brake [27], Multipole dual disc [43]) presented in the state of art is necessary. Table 3 compares the design specifications of the proposed MR clutch to the existing MR devices in the literature.…”
Section: Torque Experiments Resultsmentioning
confidence: 99%
“…Shiao et al [3] achieved a multipole compact dual disc magnetorheological brake with a simple and light weight mechanical construction and optimized the structural dimensions of the brake through electromagnetic simulations. In this study, we use some of the fixed dimensions of an earlier designed brake, as shown in Table 2, because it achieves a higher torque density and a fairly quick response.…”
Section: Mrf-140 Cg Properties Units Valuementioning
confidence: 99%
“…This innovative design incorporates electromagnetic poles surrounded by multiple coils, thereby increasing the brake torque. Subsequently, Shiao et al [2,3] proposed a unique design for a multipole multi-layer magnetorheological brake, aiming to enhance the torque density. Such high torque density designs may be more suitable for various industrial and automotive applications.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the magnetic section task to generate and change the damping force of the mount by generating a magnetic field and driving it through the MRF layers to cause resistance to the motion of the flow. The six magnetic-pole pairs used in this study was first introduced in our design of a multipole dual-disc MR brake that used structural space efficiently to produce the highest torque-to-volume ratio (TVR), to date (Shiao and Kantipudi, 2022). In this proposed mount, a new structure of the magnetic section was developed that includes six magnetic-pole pairs, two iron discs, two MRF layers, and two cases (Figure 1(b)), in which the magnetic-pole pairs work as the source of magnetic field, the iron discs function to drive the magnetic flux, and the cases are used to prevent magnetic flux leakage.…”
Section: Proposed Mr Mount Structurementioning
confidence: 99%